PEMBIAYAAN PENGELOLAAN PRASARANA JALAN DALAM ERA DESENTRALISASI DI INDONESIA - Sri Oka Rachmadita (Diponegoro University, 2012)
Roads are public utilities whose financing comes from various sources of general taxes and loan, so the return on the financing of transport infrastructure is not only from the transportation sector itself. It raises injustice in the road usage. Taxpayers are required to pay taxes in the same amount, but the loadtraffic and the intensity of road usages are different each other. One method of road infrastructure management that has been conducted by various countries is the reforms of road management by commercializing the road, take the road financing to the market mechanism by fee for service. Condition of the road infrastructure has continued to decline since the economic crisis. This condition is exacerbated by the limitation of budgeting capacity of the local government that is not possible to finance the operation and maintenance of road infrastructure and also the uncertainty of the transfer of funds from the central government. Road User Charges can be an alternative source of financing the operation and maintenance of road infrastructure depend on the allocation of Government funds for transportation sector from Vehicle Tax and Tax on Vehicles Ownership. Then road users have to pay additional fees in each liter of fuel purchases.